2024
DOI: 10.3390/ijms25021259
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Systemic Therapy for Advanced Hepatocellular Carcinoma

Narayanan Sadagopan,
Aiwu Ruth He

Abstract: Patients with advanced hepatocellular carcinoma (HCC) have several systemic treatment options. There are many known risk factors for HCC, and although some, such as hepatitis C, are now treatable, others are not. For example, metabolic dysfunction-related chronic liver disease is increasing in incidence and has no specific treatment. Underlying liver disease, drug resistance, and an increasing number of treatment options without specific biomarkers are all challenges in selecting the best treatment for each pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…In contrast, our research takes a more comprehensive approach, incorporating multiple predictive factors and applying these models to a larger cohort of patients. This broader perspective allows for a more nuanced understanding of the complex interplay between various biomarkers and their predictive value in the context of HCC immunotherapy [23,24] .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, our research takes a more comprehensive approach, incorporating multiple predictive factors and applying these models to a larger cohort of patients. This broader perspective allows for a more nuanced understanding of the complex interplay between various biomarkers and their predictive value in the context of HCC immunotherapy [23,24] .…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy is a common treatment for advanced HCC but the development of drug resistance presents a significant challenge to treatment and prognosis improvement, making the enhancement of chemosensitivity of great clinical importance (Chouhan et al 2020;Villanueva et al 2019;Bejjani and Finn 2022;Sadagopan and He 2024). Drug sensitivity analysis showed that low-risk patients respond better to cisplatin, gemcitabine, and sorafenib, while high-risk patients are more responsive to 5-fluorouracil, dasatinib, and gefitinib.…”
Section: Discussionmentioning
confidence: 99%